Analisis Manajemen Piutang di Grand Swiss Belhotel Darmo - Fiola Dwi Anggraeni; Dwi Suhartini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze receivables management at the Grand Swiss Bel-Hotel Darmo. The author conducted this research on the basis that considering the importance of receivables management in the hospitality sector. This study used descriptive qualitative method. Primary data was obtained from an interview with one of the account receivable staff. The analysis was carried out by observing (observations) from the author, which was supported by the results of interviews, and strengthened using literature studies obtained through books and journals. The results of the research show that all financial management activities have been carried out well. However, there are still several problems, namely that some records still do not use software, conditions in the field are too late, resulting in delays in data input, and customers are having difficulty making payments.